A plastic-damage model for concrete under compression. (January 2019) - Sarikaya, A.; Erkmen, R.E.
Highlights: Elastoplastic-damage model for plain concrete under compression is formulated. Partitioning of the strain tensor is proposed within the elastoplastic-damage framework. The partitioning permits the use of single failure criterion and potential surface. The model can be calibrated according to well-established plasticity rules. Proposed approach simplifies the numerical procedure by eliminating iterations. Abstract: A phenomenological model for plain concrete under compression is formulated within the framework of the coupled elastoplastic-damage theory. Phenomenological elastoplastic-damage models have been widely used for concrete because of their capability of representing both the permanent inelastic deformations and the degradation of material moduli beyond the elastic range. The essential contribution introduced in this paper is the proposed partitioning of the strain tensor within the coupled elastoplastic-damage framework which simplifies the selection of the failure surface and the potential function. Proposed partitioning permits the use of single failure criterion and single potential surface that are effective for both damage and plasticity models during inelastic deformations. Therefore, the coupled elastoplastic-damage model can be easily calibrated to fit the observed concrete behaviour based on well-established non-associated plasticity rules for concrete. The proposed approach also simplifies the numerical procedure by eliminating iterations that is required to equilibrate the stresses in plastic and damage components of the model. The numerical implementation is explained, and the results predicted by the model are compared with experimental data provided in the literature. Graphical abstract: Comparison with the experimental stress-strain results of Imran[35] for normal concrete (w/c = 0.55) under cyclic axial loading with constant confinement pressure.